Analisis Faktor Keuangan dan Non Keuangan yang Mempengaruhi Prediksi Peringkat Obligasi (Studi empiris pada perusahaan penerbit obligasi yang terdaftar di Bursa Efek Indonesia periode 2012-2014) - Putri Sakinah; Ardi Paminto; M. Amin Kadafi (Faculty of Economics and Business Mulawarman University, 2017)
The purpose of this study is to examine the effect of liquidity as measured by Current Ratio (CR), Leverage is measured by Debt to Equity Ratio (DER), guarantee and age of bonds to bond rating listed on the Indonesia Stock Exchange. The research sample used is a bond issuer company listed on the Indonesia Stock Exchange (IDX) period of 2012 to 2014. Data collection research using purposive sampling method. Data obtained by 10 companies in the period 2012 to 2014. This study used logistic regression analysis to analyze the data. The result of this research is the liquidity proxied with Current Ratio (CR) has no significant effect on the rating of bond in Indonesia Stock Exchange. The leverage proxied by the Debt to Equity Ratio significantly influences the rating of bonds on the Indonesia Stock Exchange and the age of the bonds and the guarantee does not significantly affect the rating of bonds in the Indonesia Stock ExchangeKeywords: Bonds, bond ratings, liquidity, leverage, age of bonds, guarantees